Strategy for Increasing Adoption of Enterprise Resource Planning (ERP) System at PT XYZ - Dhinda Waluya Ramadina; M. Syamsul Maarif; Nur Hasanah (Ilomata International Journal of Social Science, 2025)
The increasing complexity of business operations and the demand for efficiency have prompted PT XYZ to implement an Enterprise Resource Planning (ERP) system. However, ERP implementation often faces obstacles such as user resistance and difficulty adapting to new technologies. The research method used a direct approach. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS), followed by strategic prioritization using the Analytical Hierarchy Process (AHP). The results showed that performance expectations, social influence, and enabling conditions significantly influenced ERP usage behavior, while effort expectations did not. Based on these findings, key strategies identified included improving user training, increasing managerial involvement, and developing a more user-friendly ERP interface. The company needs to ensure that ERP delivers tangible benefits to work efficiency, supported by management commitment and adequate infrastructure. Developing a structured implementation plan and engaging top management from the outset are crucial for the system's success.